2017
DOI: 10.1111/liv.13524
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative ultrasound for prediction of hepatocellular carcinoma biological behaviour: Prospective comparison with pathology

Abstract: Background & Aims Preoperative prediction of both microinvasive hepatocellular carcinoma and histological grade of hepatocellular carcinoma is pivotal to treatment planning and prognostication. The aim of this study was to evaluate whether some intraoperative ultrasound features correlate with both the presence of same histological patterns and differentiation grade of hepatocellular carcinoma on the histological features of the primary resected tumour. Methods All patients with single, small hepatocellular ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 43 publications
2
9
0
Order By: Relevance
“…In a previous study [15], we have demonstrated that IOUS is able to detect the features of MI-HCC and these findings strongly correlated with histopathologic criteria. These IOUS findings are important to knowledge the biological behavior of HCC and to predict the risk of longterm recurrence and overall survival rates.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…In a previous study [15], we have demonstrated that IOUS is able to detect the features of MI-HCC and these findings strongly correlated with histopathologic criteria. These IOUS findings are important to knowledge the biological behavior of HCC and to predict the risk of longterm recurrence and overall survival rates.…”
Section: Discussionsupporting
confidence: 58%
“…Number of HCC nodules was also registered: in this case, IOUS pattern has been determined for the largest nodule. As described in our previous article [15], MI-HCC was defined as a tumor with vascular/biliary infiltration and/or the presence of satellites (Fig. 1).…”
Section: Ious Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…The degree of pathological differentiation re ects the extent of the malignancy [10]. The poorer the differentiation, the more disordered the tissue and vascular structure and the higher the risk of cancer cells invading the surrounding tissues [11]. Given that biomarkers seen on an MRI may re ect the heterogeneity of cancerous tissue, texture analysis of a single biomarker may have increased sensitivity and speci city [12].…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Further complicating this discussion, detection of micro-invasive disease pre-operatively remains challenging. Intra-operative ultrasound (IOUS), used frequently with superior detection of microinvasive disease compared to other pre-operative imaging modalities, 10 can result in expanded resection margins intraoperatively. We were interested in evaluating if type of resectionas stratified by wedge, single, two or three-segment resection would demonstrate the long term overall survival benefit of resection seen in prior retrospective reviews 11,12 when stratified by liver impairment and tumor size.…”
Section: Introductionmentioning
confidence: 99%